The application of FengShuiin the design of contemporary architecture and its environment - Areej Kareem Kareem Al-Sadkhan; Lena Auday Hatem (Iraqi Journal of Architecture and Planning, 2018)
1World Thisresearchdiscussascientificvisionaboutthenaturalcomponentsofthe environmentanditseffectontheurbanenvironmentandhumaninparticular,allthiswillbe discussedwithintheframeworkofanancientdisciplineknowninChinaastheartto determinethebestconditionsfortheconstruction ofbuildingsordevelopmentofcities,called "FengShui".Itisapracticaltechnique,designedtofindtherightplace,gooddirection,good shape,goodproportionandgoodarrangementfordesigningthebestenvironmentinwhichto live. "FengShui"is amean ofassessing theenvironment and providesthetechniques forlocal constructionaccordingtotheparticularitiesofeachplace.Itslonghistoryhasenabledittobe consideredasasciencerichofknowledgeandconcretewaysofworking.Thisisatechnique thattakesactionbasedonlocalconditions,includinggeographicalconditions,climate,habits and customs ofthepeople, culturebut also theexpertisein construction.ThecasestudyofthisresearchisthehighrisingbuildingsinHaifastreettobeassessed according toitsrelationshipwith thesiteandothercharacteristicsoftheareainthelargescale and then theeffectofthetransportation andtheroad system that leads to itand its relationship withthesurroundingareasespeciallytheorganicneighborhoodsbehind,finallythestudy discusstheheightandshapeofthebuildingsaccordingtotheprinciplesof"FengShui",and attheendthestudysuggests proposals forthebetterexploitation oftheenvironmental component to achievethesustainabilitythat weall need.